Dual charged folate labelled chitosan nanogels with enhanced mucoadhesion capacity for targeted drug delivery. (5th July 2020) - Guaresti, Olatz; Maiz–Fernández, Sheila; Palomares, Teodoro; Alonso–Varona, Ana; Eceiza, Arantxa; Pérez–Álvarez, Leyre; Gabilondo, Nagore
Graphical abstract: Highlights: The use of natural polymers represents a great progress in many fields. The presence of functional groups influenced the swelling and mucoadhesion. Nanogels were further functionalized via click chemistry for targeted drug delivery. Abstract: Nanometric gel particles (CsSH/PEGBCOOH) were successfully synthesized through water in oil (W/O) emulsion by the covalent cross–linking between the primary amines of thiolated chitosan (CsSH) and the dicarboxylic poly(ethylene glycol) (PEG) derivative as cross–linker (PEGBCOOH). Thus, the amidation reaction led to the formation of stable nanosized networks positively or negatively charged by the ionization of either amines or thiol moieties depending on the surrounding pH. This double response, which has not been studied before, was markedly observed and quantified during the characterization of the nanogels, concluding the high impact that could suppose these promising nanoparticles in the biomedical field. Besides, the presence of thiol groups in the nanogels was demonstrated to greatly improve the nanoparticle–mucus interactions, highlighting the potential of this novel strategy in the field of nanotechnology. Finally, nanogels were further labelled with folate ligand as an example of a simple and easy functionalization route via thiol–Michael addition (MA) reaction for future studies of tumour targeting therapies of these nanocarriers. Therefore, the synthesized chitosan–based labelled nanogels presented an adaptable character to the environmental conditions due to their dual pH response and mucoadhesion capacity, making them great candidates as nanocarriers for biomedical applications.